P, Pengaruh We hereby propose to the team our research article with the title THE INFLUENCE OF CHEST MOBILIZATION AND CHEST EXPANSION RESISTANCE EXERCISE ON EXPANSION THORACS OF PNEUMOTHORACIC PATIENTS IN THE LUNG HOSPITAL DR. M. GOENAWAN PARTOWIDIGDO, we hope that i - Hariandja, Andy Martahan Andreas; Ali, Mohammad; Satwika, Erna; Lisaninda, Annas Diah (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Pneumothorax is common in the age range of 26-45 years. More men were diagnosed with pneumothorax with a percentage of 68.8%, and women were 31.1%. Health problems in patients with pneumothorax are decreased expansion, shortness of breath, and fatigue. Chest mobilization(CM) can maximize chest wall by stretching the chest wall and chest expansion resistance exercise(CERE) which is effective for increasing thoracic expansion capacity. This research aims to determine the effect of CM and CERE on thoracic expansion in pneumothorax patients. This research uses a quasi-experimental study with a pretest posttest with control group design. samples were selected by purposive sampling method which had been determined according to inclusion and exclusion criteria as many as 16 people divided into 2 groups. Measurement using the midline. Univariate analysis to see characteristics of the sample. Bivariate analysis using paired sample t-test and independent sample t-test. The results of statistical analysis of the paired sample t-test for both groups showed significant changes in thoracic expansion with a p value of 0.000, the results of the independent sample t-test obtained a p-value 0.019 for the upper thorax and 0.025 for the lower thorax. Conclusion: CM and CERE have a significant effect on chest expansion in pneumothorax patients.